2020
DOI: 10.1111/ibi.12824
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting sensitivity of nestling and fledgling Barn Swallow Hirundo rustica body mass to local weather conditions

Abstract: Local weather can influence the growth and development of young birds either indirectly, by modifying prey availability, or directly, by affecting energetic trade‐offs. Such effects can have lasting implications for life history traits, but the nature of these effets may vary with the developmental stage of the birds, and over timescales from days to weeks. We examined the interactive effects of temperature, rainfall and wind speed on the mass of nestling and fledgling Barn Swallows Hirundo rustica both on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 78 publications
2
12
0
Order By: Relevance
“…Recent studies of Tree Swallows have found a decrease in nestling body mass with an increase in mean rainfall during the nestling period (Cox et al 2019) (Facey et al 2020). Overall, we found that Tree Swallows and Barn Swallows showed similar responses to local weather conditions in terms of breeding phenology over the four years of our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Recent studies of Tree Swallows have found a decrease in nestling body mass with an increase in mean rainfall during the nestling period (Cox et al 2019) (Facey et al 2020). Overall, we found that Tree Swallows and Barn Swallows showed similar responses to local weather conditions in terms of breeding phenology over the four years of our study.…”
Section: Discussionsupporting
confidence: 78%
“…We obtained weather data from Environment and Climate Change Canada (Government of Canada 2019) for all four years (2013-2016) from a Vancouver weather station (YVR Airport, 49°11'42.000" N, 123°10'55.000" W, elevation 4.30 m). We used data for average daily temperature (°C), average daily precipitation (mm), and average daily wind speed (km/h) as variables to represent local weather (Cox et al 2019, Facey et al 2020. We calculated averages for (1) the pre-laying period, either 2 or 4 wk (to account for the nest-building period and arrival on breeding grounds) before the first egg date for each species in each year, and (2) for the month of June, which coincided with the main chick-rearing period for first broods in both species.…”
Section: Weather Datamentioning
confidence: 99%
“…Lastly, the interaction of different weather effects may change our predictions of future change because interactions among weather variables or other changing variables could enhance or ameliorate negative effects. For example, in a study of barn swallows Hirundo rustica, nestling mass between age 8-12 days is negatively associated with increasing temperatures, and this effect is stronger during heavier rainfall, but weaker during high wind speeds (Facey et al, 2020).…”
Section: Other Components Of Weather Can Also Affect Nestling Growthmentioning
confidence: 99%
“…both positive and negative relationships can occur, depending on species and/or population) and context-dependent (i.e. differing between environments) [ 21 , 24 27 ]. One explanation of this variability may result from the fact that negative effects of adverse weather can be moderated by adjustments in parental care strategies [ 24 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%